O processo de construção de um mosaico educacional: reflexões a partir de experiências de gestão em dois contextos desafiadores - Ramos, Roberto Carlos (Universidade do Vale do Rio dos Sinos, 2015)
In this study executive experiences within geographically and culturally very distinct realities are described – Mangunde in Mozambique and Scampia in Italy – where the daily challenges were useful to give ground to innovating projects. In order to identify the characteristics of the “I manager” that develops a reflective attitude throughout the work. To this end, the dissertation rests basically on two theoretical: Alberto Melucci the first inviting him to glance at the subject, his own experience and the relationship between himself and the world in the attempt to build his identity. Paulo Freire conceived the educative praxis seen in its social dimension, under the sphere of inter-subjectivity and inter-cultural education. The Freire's approach, as in intrinsic part of the experiences lived by me, now takes new vigor, enabling the development of more solid reflections on the constitution process of the self-manager. With the mosaic metaphor, the text is being built with different shades and shapes. Among the results of this reflective process suggestions arise to the future managers of the educational field. Among the results of the reflective process emerge suggestions to future managers in the educational field, such as capacity of inserting himself into the processes, of knowing them deeply, and standing back of them, in order to analyze them with sense and supported by intellectual partners, that offer theoretical sources as subjects of reflecting. Involving oneself entirely into the daily context, but being at the same time attentive to the temptation of not being totally absorbed by it. Returning to the metaphor, the mosaic has been, and ever will be, built and observed within a constant movement of approach and standing back. The secret consists in seeing, hearing, dreaming and acting with hope. Who knows, much more than verbs, they consist in principles of action for those who assume the challenge of educational managing.
Keywords: Gestão educacional; Prática reflexiva; Eu-gestor; Educational management; Reflexive praxis; Myself executive; ACCNPQ::Ciências Humanas::Educação